GUBERNIA REFORM IN RUSSIA ON THE VERGE OF 18th AND 19th cc - L. Sh. Kuanchaleyeva (Russian Journal of Economics and Law)
The article is devoted to the historic-legal analysis of legislative bases of gubernia administration in Russia on the verge of 18th - 19th cc. Basing on the research of the most important normative-legal acts, the article shows that the changes in the administrative-territorial structure of the country and local administration can, by their character and content, be viewed as anew gubernia reform.